PENYEBAB KONFLIK RUMAH TANGGA PADA KLIEN SATRIA UTAMA RELATIONSHIP COACH - Muhammad Faiz Hasyfi Prayogo (Universitas Prof. Dr. Moestopo (Beragama), 2020)
in improving family relations quality. This research aims to know causes of conflict in the family by a relationship coach. This research is using phenomenological method to obtain in-depth data from informant who experience in providing consultancy in domestic life named Satria Utama whom establish a relationship coach for seven years. Collecting data methods that is used for this research is in-depth interview and its analyzed with phenomenological research steps. There are three factor that causing marital conflict: genderlect styles, encoding-decoding process in communicate feelings, and family communication pattern. This analysis conclude that the three factor is a unity and cannot be separated. The communication differentiation between man and woman that occur is not about dialectic, but man and woman speak with different genderlect. One way to improve marital communication quality is a safe feeling in expressing feelings. Many people cannot express their feelings clearly to their spouse, so they need a coach to describe their feelings verbally based on some situation. Parents also affect how their kids marital relationship later when they grow up. Conflicts that happen in marriage relationship cannot be separated from how their parents communication pattern with their kids when they were kids.